Implementating Management Information System And Supervision at The AMIK Depati Parbo Kerinci - Sandra, Elvina; Sestriyenti, Enny; R, Ferdinal (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study aims to evaluate the extent of the implementation of the Management Information System (MIS) at AMIK Depati Parbo Kerinci and the supervision conducted to address issues of operational efficiency, management effectiveness, and service quality for users (students, lecturers, and staff), which may hinder campus progress at internal and external levels. Methodology: The research employs a descriptive method with a qualitative approach based on a case study regarding the use of MIS in Academic, Financial, and Personnel activities at AMIK Depati Parbo Kerinci. Results: The implementation of MIS at the campus supports academic, financial, and personnel activities synergistically, although challenges in supervision and coordination require enhancement to ensure better integration. Findings: The study reveals that consistent supervision is key to optimizing the effectiveness and efficiency of MIS usage in higher education institutions. Novelty: This research provides new guidelines on the importance of supervision in the implementation of MIS in higher education. Originality: The study highlights the need for integrated supervision strategies to enhance MIS operational efficiency. Conclusions: Effective supervision can overcome barriers in MIS implementation, support operational efficiency, and improve user services at AMIK Depati Parbo Kerinci. Type of Paper: Empirical research paper.